N. meningitidis 1681 is a member of the FinO family of RNA chaperones - Chaulk, Steven (Landes Bioscience, 2010)
The conjugative transfer of F-like plasmids between bacteria is regulated by the plasmid-encoded RNA chaperone, FinO, which facilitates sense—antisense RNA interactions to regulate plasmid gene expression. FinO was thought to adopt a unique structure, however many putative homologs have been identified in microbial genomes and are considered members of the FinO_conjugation_repressor superfamily. We were interested in determining whether other members were also able to bind RNA and promote duplex formation, suggesting that this motif does indeed identify a putative RNA chaperone. We determined the crystal structure of the N. meningitidis MC58 protein NMB1681. It revealed striking similarity to FinO, with a conserved fold and a large, positively charged surface that could function in RNA interactions. Using assays developed to study FinO-FinP sRNA interactions, NMB1681, like FinO, bound tightly to FinP RNA stem-loops with short 5′ and 3′ single-stranded tails but not to ssRNA. It also was able to catalyze strand exchange between an RNA duplex and a complementary single-strand, and facilitated duplexing between complementary RNA hairpins. Finally, NMB1681 was able to rescue a finO deficiency and repress F plasmid conjugation. This study strongly suggests that NMB1681 is a FinO-like RNA chaperone that likely regulates gene expression through RNA-based mechanisms in N. meningitidis.